Survival in patients with hepatocellular carcinoma treated with 90Y-microsphere radioembolization - Sabet, A.; Ahmadzadehfar, H.; Bruhman, J.; Sabet, A.; Meyer, C.; Wasmuth, J.-C.; Pieper, C.-C.; Biersack, H.-J.; Ezziddin, S. (Nuklearmedizin - NuclearMedicine, 2014)
Aim: This retrospective study aims to evaluate the predictive value of FDG PET/CT in patients with unresectable hepatocellular carcinoma (HCC) undergoing radioembolization with yttrium-90 labeled microspheres (RE). Patients, methods: The study cohort comprised 33 patients who were treated with RE at our institution and underwent FDG PET/CT at baseline and four weeks after radioembolization. According to the baseline FDG metabolic status of the HCC lesions, patients were divided into two groups: FDG-negative (n = 12) and FDG-positive (n = 21) HCC. FDG-positive patients were further divided into early metabolic responders and non-re- sponders according to the relative change in SUVmax of the treated lesions. Survival analyses were performed with the Kaplan-Meier method (log-rank test, p < 0.05). Multivariate analysis was performed to assess the influence of prognostic factors on overall survival (OS). Results: FDG-negative patients had a significantly longer OS (13 months, 95%CI 7-19) than FDG-positive patients (9 months, 95%CI 7-11; p = 0.010). Among FDG- positive patients, metabolic responders survived significantly longer than metabolic non- responders (10 months, 95%CI 8-12 vs. 5 months, 95%CI 4-6; p = 0.003). From the other baseline factors (including performance status, hepatic tumour burden, presence of extra-hepatic disease, administered activity) only the BCLC stage had a significant impact on OS (p = 0.028). Conclusion: Pre- and post- therapeutic FDG PET independently predicts overall survival in patients with HCC undergoing radioembolization. Interestingly, early metabolic response seems to be assessable as early as four weeks post-treatment.
Keywords: 18F-FDG PET; radioembolization; SIRT; HCC